1991
DOI: 10.1095/biolreprod44.3.448
|View full text |Cite
|
Sign up to set email alerts
|

Puberty in the Male Chimpanzee: Progressive Maturation of Semen Characteristics1

Abstract: Cellular and biochemical characteristics of semen obtained by masturbation were studied in 5 pubertal chimpanzees during 1.5 yr. The dental age corresponding to the beginning of the pubertal testicular growth (Po) ranged from 5.0 to 8.3 years (mean = 6.7 +/- 1.2 yr). Time-related variations of all studied parameters were analyzed according to Po and, therefore, independently of the dental age. The emission of first ejaculates, and therefore the onset of activity of the accessory sex gland, was estimated to occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…In the chimpanzee, several studies found significant increases in DHEA or DHEAS in prepubertal/pubertal groups (Cutler et al 1978, Smail et al 1982 or prepubertal chimpanzees alone (Copeland et al 1985), when compared with younger age groups. These much cited results suggest that a rise in adrenal androgen levels may occur as early as 3-4 years, several years before the onset of puberty (Copeland et al 1985, Marson et al 1991. However, studies reporting individual hormone levels (rather than age-specific groups) found no discernible increase in DHEA or DHEAS during the peripubertal period (Nadler et al 1987, Bernstein et al 2012.…”
Section: Endocrinological Adrenarchementioning
confidence: 98%
“…In the chimpanzee, several studies found significant increases in DHEA or DHEAS in prepubertal/pubertal groups (Cutler et al 1978, Smail et al 1982 or prepubertal chimpanzees alone (Copeland et al 1985), when compared with younger age groups. These much cited results suggest that a rise in adrenal androgen levels may occur as early as 3-4 years, several years before the onset of puberty (Copeland et al 1985, Marson et al 1991. However, studies reporting individual hormone levels (rather than age-specific groups) found no discernible increase in DHEA or DHEAS during the peripubertal period (Nadler et al 1987, Bernstein et al 2012.…”
Section: Endocrinological Adrenarchementioning
confidence: 98%
“…Testicular volume (TV) was calculated using the formula (MARSON et al, 1991a), TV=pIAVEL/6, in which pi is the circular constant. As a rule, the right testis was measured, but for some chimpanzees with asymmetrical testes, both testes were measured and the mean TV was used for the analysis.…”
Section: Testicular Sizementioning
confidence: 99%
“…As for the chimpanzees reared at the Centre International de Recherches M6dicales de Franceville (CIRMF) in Gabon, MARSON et al (1991a) found adolescent growth spurt of body weight in males. They rearranged individual growth curves at the age when the testis started rapid growth, and the weight-gain increased clearly in males.…”
Section: Adolescent Phasementioning
confidence: 99%
See 1 more Smart Citation
“…Attempts to define puberty led to the notion that this developmental process does not readily lend itself to definition (Ojeda et al 1980). For example, Bronson and Rissman (1986) defined puberty as the onset of fertility and the period of rapid development that precedes it; for Marson et al (1991) puberty in human beings is a period of transition between the infantile stage and adulthood; Le Bail (1986) defined the start of puberty in salmonid fishes as the appearance of the first spermatocytes; several other definitions can be found in literature (Crim and Evans 1983;Schreibman et al 1986;Williamson et al 1990;Renaville et al 1993;Schulz et al 1994a). In the present study, we will consider pubertal development in male African catfish, Clarias gariepinus, as the period that starts with appearance of spermatocytes and ends with the appearance of the first spermatozoa in adolescent males.…”
Section: Introductionmentioning
confidence: 99%